2006
DOI: 10.1099/ijs.0.64517-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides barnesiae sp. nov., Bacteroides salanitronis sp. nov. and Bacteroides gallinarum sp. nov., isolated from chicken caecum

Abstract: Eight bacterial strains isolated from the caecum of chicken, BL2T, BL66, EG3, EG6, M27, BL78T, C35T and C43, were characterized by determining their phenotypic characteristics, cellular fatty acid profiles, menaquinone profiles and phylogenetic positions based on 16S rRNA gene sequence analysis. 16S rRNA gene sequence analysis showed that these isolates belonged to the genus Bacteroides. One group of five strains (BL2T, BL66, EG3, EG6 and M27) was related most closely to Bacteroides coprocola JCM 12979T, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 32 publications
1
75
0
1
Order By: Relevance
“…Previous studies have shown that the microbial diversity in chicken caecum was mainly dominated by Bacteroides, which was consistent with our study1223. Bacteroides is thought to play a fundamental role in the breakdown of complex polysaccharides, starch and cellulose into simpler compounds27. The treatments of cassava foliage increased the abundance of Bacteroides.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that the microbial diversity in chicken caecum was mainly dominated by Bacteroides, which was consistent with our study1223. Bacteroides is thought to play a fundamental role in the breakdown of complex polysaccharides, starch and cellulose into simpler compounds27. The treatments of cassava foliage increased the abundance of Bacteroides.…”
Section: Discussionsupporting
confidence: 92%
“…(Huang et al, 2013); 6, Marinilabilia (Krieg, 2011;Shalley et al, 2013); 7, Bacteroides (Lan et al, 2006;Robert et al, 2007;Hayashi et al, 2007;Chassard et al, 2008;Ueki et al, 2008Ueki et al, , 2011Nishiyama et al, 2009;Watanabe et al, 2010;Kim et al, 2010;Kitahara et al, 2011Kitahara et al, , 2012Krieg, 2011;Sakamoto & Ohkuma, 2013 catalase-positive. NaCl is required for growth.…”
Section: Strains Fh5mentioning
confidence: 99%
“…Phenotypic characterization and 16S rRNA gene analysis has been found to be promising in identifying novel bacterial species in avian GI tract [45]. Furthermore, from mammalian GI tract some novel hydrolases [46,47] and polyphenol oxidases [48] have been identifi ed.…”
Section: The Function-driven Analysismentioning
confidence: 99%